Performance of Irrigated Soilless and Field-Grown Pea (Pisum sativum) in Possotomé, Benin: A Comparative Study (Sciences et Technologies pour l’Agriculture Durable, 2026)
Food security relies on an agricultural production system increasingly exposed to climate variability. Ensuring food security necessarily requires the sustainable intensification of production systems. However, this intensification must occur in a context of declining availability of arable land and water resources, which justifies the growing interest in soilless cultivation systems. Although this technique offers potential advantages for sustainable development, it remains understudied in Benin, limiting the justification for its large-scale adoption. This study aims to compare the agronomic performance of pea (Pisum sativum) cultivated in soilless and open-field systems. An experimental design with separated plots was implemented, testing two factors: irrigation rate and organic fertilization rate (poultry manure). Growth parameters (leaf number and plant height) were monitored weekly from emergence until the sixth week, and yield was evaluated at harvest. The results indicate that the soilless system, with only 16.8 L/16.1 m², induced better growth performance than the conventional system, despite the latter using nearly four times more water (66 L/16.1 m²). Furthermore, organic fertilization enhanced water productivity in soilless cultivation compared to the conventional system. These results highlight the potential of soilless cultivation as a sustainable alternative for pea production in Benin.
Keywords: Soilless cultivation; Poultru manure; Separate plots experimental design; Pisum Sativum; Southwestern Benin